Research on the marketing strategy of Shaanxi Xifeng Distillery Co., Ltd. in the context of e-commerce - Liu, Xuanrui; Bi, Chuanchen (Technium Social Sciences Journal, 2022)
In today's network information age, the vigorous development of e-commerce has brought great opportunities and challenges to the development of marketing. This paper first analyzes many problems faced by marketing in the context of e-commerce, and then puts forward a series of new marketing strategies in the context of e-commerce, in order to be able to deal with the opportunities and challenges of marketing in the era of e-commerce.Based on the research logic of "discovering problems, investigating and analyzing problems, and solving problems", this study discusses from five aspects. Firstly, from the actual background of e-commerce marketing, the development process of e-commerce marketing and the development status and development trend at home and abroad are analyzed. Secondly, the relevant basic theories are elaborated, and the advantages and characteristics of e-commerce marketing are explained in detail. In-depth analysis of the current operation status of Shaanxi Xifeng Distillery Co., Ltd., comprehensive diagnosis of the marketing strategy of its main products, and detailed discussion of the competitive environment for enterprises to develop e-commerce marketing. Finally, the implementation steps of the enterprise's e-commerce marketing strategy are broken down in detail. After comprehensively using the literature research method, survey research method, SWOT analysis method and interview method to analyze the existing problems of Shaanxi Xifeng Distillery Co., Ltd., the following conclusions are mainly obtained.